Learning Curve and Initial Outcomes of Full-Endoscopic Posterior Lumbar Interbody Fusion - Tan, Renchun; Lv, Xin; Wu, Pengfei; Li, Yawei; Dai, Yuliang; Jiang, Bin; Ren, Bolin; Lv, Guohua; Wang, Bing (Frontiers in Surgery, 2022)
Low back pain is one of the crucial medical conditions worldwide. FE-PLIF has been reported to be a minimally invasive method to treat mechanical low back pain, but there lacks a thorough evaluation on this new technique.The patients were divided into three groups in the order of operating date.The data of patients were reviewed for gender, age, preoperative symptoms, satisfaction, as well as clinical outcomes demonstrated by visual analog scale (VAS). The operative time and intraoperative fluoroscopy were recorded to demonstrate the learning curve and the extent of radiographic exposure.The average number of intraoperative fluoroscopy was 6.79 ± 0.72. A significant improvement was observed in the VAS of both lumbar pain and leg pain. The overall fusion rate was 77.7%. The average operative time showed a trend of gradual decline. The learning curve was characterized using a cubic regression analysis as y = –48.09x + 3.92x2–0.10x3 + 551.11 (R2 = 0.387, p = 0.018).FE-PLIF is an effective and safe method for treating low back pain caused by short-segmental degenerative diseases. The learning curve of this technique is steep at the initial stage but acceptable and shows great potential for improvement.